(untitled) (Az-Zaida: Jurnal Ilmu Multidisiplin, 2026)
This study aims to analyze human resource management practices in madrasas that integrate humanization, educational quality, and the trustworthy ethos as a discursive space for Islamic education. The study employed a qualitative approach with a single case study at Madrasah Tsanawiyah Al-Hikmah, collecting data through in-depth interviews, participant observation, and documentation studies. The results indicate that teacher humanization, the socio-religious construction of educational quality, and the internalization of the trustworthy ethos create a participatory work climate and enhance teacher professionalism. This study’s contribution lies in providing a holistic perspective on human resource management based on Islamic educational values that can serve as a reference for developing teacher management policies and practices.